2013
DOI: 10.1111/gcbb.12045
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization to optimize the greenhouse gas balance of hemp crops grown for biomass

Abstract: Nitrogen trials were carried out on hemp crops grown in Ireland over a 3 year period to identify nitrogen fertilization strategies which optimize the greenhouse gas (GHG) and energy balances of hemp crops grown for biomass. Nitrogen rates up to 150 kg N ha À1 were used in the study. Yield increased with nitrogen rate up to 120 kg N ha À1 for early (Ferimon), mid (Felina 32) and late maturing (Futura 75) varieties. Variety had a significant effect on yield with yields increasing with maturation date. In 2 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 18 publications
0
33
1
Order By: Relevance
“…Hemp is considered an ideal annual crop for the bio‐economy as it has the potential to produce a high multipurpose biomass yield while requiring little inputs (Finnan & Burke, ; Tang et al ., ). However, very limited information is available on the physiological basis of hemp resource‐use efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemp is considered an ideal annual crop for the bio‐economy as it has the potential to produce a high multipurpose biomass yield while requiring little inputs (Finnan & Burke, ; Tang et al ., ). However, very limited information is available on the physiological basis of hemp resource‐use efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The high photosynthesis rate of hemp at low nitrogen condition is in line with its observed high productivity at low nitrogen input (Struik et al ., ; Finnan & Burke, ) and puts hemp ahead of cotton and kenaf from a perspective of bio‐economy. However, our model approach has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research also showed that hemp response to P might vary depending on growing conditions [70], and its availability plays an important role in the elasticity and tensile strength of hemp fibers. A study reported that P uptake by hemp ranged from 52 to 67 kg ha −1 , and P fertilization had no effect on stem yield [67]. P enhancement treatment caused a 16% reduction of THC concentration but did not affect CBD concentration in the flowers [71].…”
Section: Effect Of Phosphorusmentioning
confidence: 99%
“…A study reported that 79% of total N uptake occurred within the first month with a daily N uptake of 3-4 kg ha −1 [66]. Another study reported that N application after sowing or applied by split method did not increase stem yield when compared to N distribution at sowing [67]. An increase in 60 kg dry matter (stem biomass) kg −1 N applied was noticed as N fertilization was increased from 0 to 120 kg N ha −1 .…”
Section: Effect Of Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation